Kinerja Jangka Panjang Kolom Hasil Perbaikan Dengan Bahan Tambah Bonding Adhesive Agent - Cindy Deniswara; Richardo Pelipus Boru Ratomesang; Rr.M.I. Retno Susilorini; Budi Santosa (Universitas Katolik Soegijapranata Semarang, 2017)
The research was conducted to investigate the performance of old repaired columns inSriwulan Village (Sayung) and Pucang Gading. The performance of 3 columns wasinvestigated by non destructive test and destructive test at age of repaired columns at 12, 13,and 14 months. Non destructive test conducted by Hammer Test while destructive testconducted by Core Drill Test. The results of research has shown that from Hammer Test,highest compressive strength at age 14 months was 45,65 MPa. For Core Drill Test results,the highest compressive strength 73,62 MPa found in Pucang Gading at column 1 at zone A byage 14 months while the lowest at same site and column at zone C 14,22 MPa